1997
DOI: 10.1021/la960960s
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Structure of CaCO3 Scale Layers Formed under Isothermal Flow Conditions

Abstract: The morphology and the growth pattern of calcium carbonate deposits formed on inner pipe surfaces, under turbulent flow, are studied. At temperatures below 30 °C, and for relatively high supersaturations, quite compact calcite layers are obtained, consisting of crystals growing nearly perpendicularly to the substrate surface in a columnar pattern. For small supersaturations (i.e., below a critical value S c ∼ 7), the deposition rate is drastically reduced and large isolated crystals are formed. At temperatures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
16
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 12 publications
7
16
0
Order By: Relevance
“…This value is reasonably close to the supersaturation level (pH 8.3 and S = 4.3) at which scaling is first observed in the flow of CaCO 3 supersaturated solutions in pipes, with the same water quality [10,23].…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…This value is reasonably close to the supersaturation level (pH 8.3 and S = 4.3) at which scaling is first observed in the flow of CaCO 3 supersaturated solutions in pipes, with the same water quality [10,23].…”
Section: Resultssupporting
confidence: 79%
“…7c and d). The dominant phase in the deposits seems to be influenced by the solution pH, as already observed in pipe flow experiments [23].…”
Section: Scale Morphologysupporting
confidence: 65%
“…5, are consistent with those reported in the literature [26,27]. The morphologies of CaCO 3 polymorphs observed in the present work are also similar to those found in other studies [6,22,[29][30][31][32][33]. Only calcite and vaterite crystals were found on Cu after exposure in the control test.…”
Section: Control Testsupporting
confidence: 93%
“…This result may indicate a lower scaling rate for Teflon, but given that the polymer has a low thermal conductivity, the formation of small amounts of calcium carbonate is not likely to have a dramatic effect on the thermal performance. Andritsos et al [22] compared scaling on stainless steel, copper and Teflon tubes, and found that the surface had little effect. However, the experimental conditions led to a diffusion-controlled mechanism in which the surface is not expected to impact the process.…”
Section: Introductionmentioning
confidence: 99%
“…6). Development of similar distinct rhombohedral structure of calcite crystals was reported in other studies (Andritsos et al 1997;Kitamura 2001). This phenomenon can be associated with the continuous precipitation and accumulation of sparing soluble salts on the membrane surface.…”
Section: Morphological Resultssupporting
confidence: 82%